Graphite Nanoplatelets Nanostructured Films as Multifunctional Protective Layer in Kevlar/Nomex Sandwich Composites - Fabrizia Cilento; Barbara Palmieri; Giovangiuseppe Giusto; Ruggiero Volponi; Giovanni Bruno; Carmine Carandente Tartaglia; Cinzia Toscano; Michele Giordano; Alfonso Martone (Applied Sciences, 2023)
In the aerospace sector, structural and non-structural composite components are usually subjected to a wide range of environmental conditions. Among all, moisture can seriously damage these materials’ performance, reducing their mechanical, thermal, electrical, and physical properties as well as their service time. Lightweight protective barrier coatings capable of reducing the diffusion of gases and/or liquids in a material can improve the material’s resistance in humid environments. In this work, nanolamellar nanocomposites characterized by a high in-plane orientation of nanoplatelets have been employed as protective coatings for Kevlar sandwich panels, reproducing the construction of a nacelle engine. The effectiveness of the protection against water uptake of nanocomposites reinforced with graphite nanoplatelets (GNPs) at high filler contents (70, 80 and 90 wt%) has been investigated using moisture uptake and Ground-Air-Ground (GAG) tests in an environmental chamber. GNP coatings effectively work as barrier by generating highly tortuous paths for molecule diffusion. Results showed a dependence of the absorption on the coating composition and inner structure. Films @70 wt% GNPs showed the best protection against moisture uptake by delaying the phenomenon and reducing the absorption by −80% after 3 days and −35% after 41 days.